Exchange rate and macroeconomic aggregates in Nigeria (2012)
This study analyses the impact of exchange rate on macroeconomic aggregates in Nigeria. Based on the annual time series data for the period 1970 to 2009, the research examines the possible direct and indirect relationship between the real exchange rates and GDP growth. The relationship is derived in two ways using a simultaneous equations model within a fully specified (but small) macroeconomic model, and a vector-autoregressive model. The estimation results show that there is no evidence of a strong direct relationship between changes in the exchange rate and GDP growth. Rather, Nigeria’s economic growth has been directly affected by fiscal and monetary policies and other economic variables particularly the growth of exports (oil). These factors have tended to sustain a pattern of real exchange rate over-valuation, which has been unfavourable for growth. The conclusion is that improvements in exchange rate management are necessary but not adequate to revive the Nigerian economy. A broad program of economic reform is required, which includes among others, a complementary restrictive monetary policy. On the whole, the results are informative.